Study of histopathological changes in brian of mice infected with Toxoplasma gondii isolated from domestic rabbit: Raghad Ibraheam Khalil AL-Mahdawi1, Alia Yousif Yakoob1 and Rajiha abd Alsattar2 - AL-Mahdawi, Raghad Ibraheam Khalil (The Iraqi Journal of Veterinary Medicine, 2015)
The study was designed to determine the infection rate of Toxoplasma gondii in the rabbits and histopathological changes of infected internal organs in mice. A total of 60 blood samples were collected from clinically healthy rabbits from different region of Baghdad city for the serological detection of T. gondii infection. Biological assay in mice was performed by intraperitoneal inoculation of 0.1 ml digested organs suspension, (lungs, heart, liver, spleen, kidney, muscles, and brain) during the period from October 2013 until July 2014. The results revealed histopathological changes in bioassay mice infected by T. gondii isolated from domestic rabbit, no histopathological changes in the brain of animals of first group1 (control group), but in the group 2 (killed at day 15) the main pathological changes were perivascular perineuronal edema with presence of some degenerated neurons characterized by shrunken dark blue stained (basophilic) cell bodies. In the animals of the group 2 (killed at day 21) the main brain histopathological changes were Sever congestion of meningeal blood vessels with infiltration of inflammatory cells and focal aggregation of microglial cells with diffuse obvious focal gliosis, whereas, in the same group animals that killed at day 28 the main brain histopathological changes were focal encephalomalacia and edema between molecular and granular layer.